Intellectual Property, Copyright, and Plagiarism: Propiedad intelectual, derecho de autor y el plagio - Carcausto, Wilfredo (2019)
This article aims to provide a brief description of some basic concepts related to intellectual property and copyright as established by the World Intellectual Property Organization. In the Peruvian context, these concepts are also addressed in Legislative Decree No. 822 – Copyright Law, the Penal Code, and by the National Institute for the Defense of Competition and Protection of Intellectual Property.